Exploring how key performance indicators influence nursing and midwifery practice: A mixed‐methods study. (21st September 2021) - Gray, Olivia; McCance, Tanya; Brown, Donna
Abstract: Aims: To scope the key performance indicators (KPIs) used in nursing and midwifery across the United Kingdom and Republic of Ireland and explore how they influence practice in healthcare organizations. Design: The study adopted a sequential, exploratory mixed‐methods design. Methods: Phase 1 incorporated a multiple‐choice questionnaire completed by 77 Directors of Nursing recruited using voluntary response sampling. In phase 2, 35 nurses and midwives who were working at executive, senior manager and clinical levels, participated in semi‐structured interviews. Data collection of both phases was conducted from January 2016 to October 2016. Findings: Quantitative data revealed over 100 nursing and midwifery‐specific KPIs. National requirements were a deciding factor in KPI selection, while clinical involvement was mainly through data collection. Respondents stated that they used patient experience KPIs, but only one was assessed as valid. Thematic analysis identified two themes: The leadership challenge (including 'voiceless in the national conversation', 'aligning KPIs in the practice context' and 'listening to those who matter'); and taking action (including 'establishing ownership and engaging staff', 'checks and balances' and 'closing the loop'). Conclusion: The large volume of KPI measurement taking place makes meaningful evaluation of performance and quality of care difficult, both in and across organizations. Nurses and midwives require enhanced knowledge of the nature and purpose of KPIs, as evidence gained from KPI data collection is insufficient to lead to improvements in practice. A practice context that encourages collective leadership, where multiple sources of evidence are gathered and everyone is included in KPI evaluation and subsequent decision‐making, is key. Impact: This study adds to the body of evidence on KPI understanding. It informs the future effective management of indicators that will facilitate the delivery of meaningful care and reduce the cost, time and effort invested in the implementation of KPIs and data management.